Back Contact Engineering for Increased Performance in Kesterite Solar Cells. Issue 15 (2nd May 2017) - Antunez, Priscilla D.; Bishop, Douglas M.; Lee, Yun Seog; Gokmen, Tayfun; Gunawan, Oki; Gershon, Talia S.; Todorov, Teodor K.; Singh, Saurabh; Haight, Richard
Abstract : The thin‐film photovoltaic absorber Cu2 ZnSn(S, Se)4 (CZTSSe) holds considerable promise for large scale conversion of sunlight into electricity. CZTSSe is composed of Earth‐abundant elements that exhibit low‐toxicities, but improvements in device efficiency have been hampered by difficulties in increasing open circuit voltages ( V OC ) due, at least in part, to disorder induced band tailing. We present a method to increase V OC through direct modification of the back contact; our approach involves the separation of fully functioning devices from their Mo/glass substrate to reveal the back CZTSSe surface. Formation of a new back contact consisting of a thermally deposited high work function material (MoO3 ), together with a higly reflective (Au) capping layer, creates an electrostatic field that drives electrons to the front p‐n junction and leads to a decrease in electron‐hole recombination. Model simulations indicating an increase in V OC with decreasing absorber thickness are borne out by experiments with devices of varying thicknesses (0.7–2.0 μm). We report V OC increases of up to 49 mV for a 1 μm thick absorber, with even greater increases up to 61 mV when the back CZTSSe surface is etched with bromine‐methanol. Abstract : High performing kesterite photovoltaic devices show improved efficiency parameters after exfoliation and back contact engineering. The use of a high work function material (MoO3 ) and a reflective back contact (Au) results in higher open circuit voltage ( V OC ) and short circuit current ( J SC ), which closely match model simulations.